1996
DOI: 10.1111/j.1558-5646.1996.tb03893.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Unisexuality in the Hawaiian Flora: A Test of Microevolutionary Theory

Abstract: Abstract.-The evolution of separate sexes as a means of avoiding self-fertilization requires the controversial coexistence of large inbreeding depression and high selfing rate in the ancestral hermaphrodite population. Fitness components of adult females and hermaphrodites in nature, of their open-pollinated progeny, and of experimental selfs and outcrosses onto hermaphrodites were compared in endemic Hawaiian Bidens sandvicensis, all of whose known populations are gynodioecious, consisting of a mixture of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 76 publications
4
49
0
Order By: Relevance
“…However, our data showing high rates of inbreeding depression despite frequent self-fertilization are consistent with estimates of inbreeding depression and outcrossing rates in at least one other gynodioecious perennial (Bidens sandvicensis; Schultz & Ganders, 1995) and in many other plants with more conventional breeding systems. Husband & Schemske (1995) compiled estimates from the literature on inbreeding depression and its correlation with outcrossing rate and life history (annual, shrubby perennial, woody perennial).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, our data showing high rates of inbreeding depression despite frequent self-fertilization are consistent with estimates of inbreeding depression and outcrossing rates in at least one other gynodioecious perennial (Bidens sandvicensis; Schultz & Ganders, 1995) and in many other plants with more conventional breeding systems. Husband & Schemske (1995) compiled estimates from the literature on inbreeding depression and its correlation with outcrossing rate and life history (annual, shrubby perennial, woody perennial).…”
Section: Discussionsupporting
confidence: 75%
“…In their study, as in this one, inbreeding depression values measured by the experimental approach were lower than those estimated by electrophoresis, although both approaches suggested that the fitness consequences of selfing were severe. In Bidens sandvicensis, the mean level of inbreeding depression measured experimentally was 0.91 whereas electrophoretic evidence indicated no excess homozygosity relative to Hardy-Weinberg expectations among adult plants despite populationlevel selfing rates averaging 0.61 (Schultz & Ganders, 1995). Thus inferred levels of inbreeding depression in Bidens, if calculated, would not differ from unity and would slightly exceed values measured experimentally.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, stable persistence of male-sterility factors in the absence of a fecundity advantage would require a combination of very high levels of inbreeding depression and extensive hermaphrodite selfing (Lloyd, 1975;Charlesworth and Charlesworth, 1978). Simultaneous occurrence of extensive selfing of hermaphrodites and high inbreeding depression has also been reported for other gynodioecious plants like Plantago coronopus (Wolff et al, 1988), Cucurbita foetidissima (Kohn, 1988;Kohn and Biardi, 1995), Bidens sandvicensis (Schultz and Ganders, 1996), and Schiedea adamantis (Sakai et al, 1997). Results of this study are fully consistent with these expectations and indicate that explanations for the persistence of females in gynodioecious D. laureola need not be sought beyond the conventional theoretical framework.…”
Section: Discussionmentioning
confidence: 99%